Augmented Chemical Reactions: 3D Interaction Methods for Chemistry - Maier, Patrick; Klinker, Gudrun (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Supporting chemistry students in learning and researchers in developing and understanding new chemical molecules is a task that is not that easy. Computer applications try to support the users by visualizing chemical properties and spatial relations. Thus far, there mostly exist applications that are controlled by using ordinary input devices as mice and keyboards. But these input devices have one problem: they always try to map a lower degree of freedom to 6-dimensional movements for the location and the orientation of the virtual molecules. Augmented Chemical Reactions is an application that uses Augmented Reality to visualize and interact with the virtual molecules in a direct way. With the introduced 3D interaction methods, the work of students and researchers is tried to be simplified to concentrate on the actual task.